On the use of sterilisation bonds in emerging Asia - Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
We document recent developments in the use of sterilisation bonds by six central banks in emerging Asia, and discuss the implications for monetary policy and the financial sector. An important development in the sterilisation of foreign exchange interventions in past years has been the frequent use of central banks' own paper. There has been an attempt to lengthen the maturity structure of sterilisation bills, and maturities have risen, especially in 2010-11. The choice of sterilisation instrument is likely to depend partly on their relative costs. In particular, as the yield on central bank securities has fallen relative to the rate of remuneration of required reserves, some central banks in Asia have increasingly used central bank securities for sterilisation.
URN:NBN:fi:bof-201408072141
Keywords: E43; E50; E52; E58; 330; sterilisation bond; central bank bonds and bills; foreign exchange reserves; emerging Asia